2013
DOI: 10.1093/ije/dyt208
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of environmental and behavioural factors associated with all-cause mortality in the United States National Health and Nutrition Examination Survey

Abstract: Our association study suggests that, of the set of 249 factors in NHANES, physical activity, smoking, serum lycopene and serum/urinary cadmium are associated with all-cause mortality as identified in previous studies and after controlling for multiple hypotheses and validation in an independent survey. Whereas other NHANES factors may be associated with mortality, they may require larger cohorts with longer time of follow-up to detect. It is possible to use a systematic association study to prioritize risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 46 publications
1
98
0
Order By: Relevance
“…In a separate analysis of the same NHANES 1999-2000 dataset, Patel et al (2013) found an association of Cd exposure and shortening of leucocyte telomeres, similar to the report of Zota et al (2015). In addition to Cd exposure, leukocyte telomere lengths showed an inverse association with serum CRP levels, physical activity, and trunk fat (Patel et al 2016).…”
Section: Cadmium -Mechanisms Of Toxicitysupporting
confidence: 65%
See 4 more Smart Citations
“…In a separate analysis of the same NHANES 1999-2000 dataset, Patel et al (2013) found an association of Cd exposure and shortening of leucocyte telomeres, similar to the report of Zota et al (2015). In addition to Cd exposure, leukocyte telomere lengths showed an inverse association with serum CRP levels, physical activity, and trunk fat (Patel et al 2016).…”
Section: Cadmium -Mechanisms Of Toxicitysupporting
confidence: 65%
“…Chronic, low-level Cd exposure in Sweden has been linked to an increased risk of heart failure (Borne et al 2015), while chronic, low-level Cd exposure in the U.S. been linked to death from CVD, heart disease, and coronary heart disease (Tellez-Plaza et al 2012) along with increased death from all causes (Hyder et al 2013;Patel et al 2013), cancer (Adams et al 2012;Lin et al 2014), and Alzheimer's disease (Min and Min 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations